From Text, to Myth, to Meme: Penny Dreadful and Adaptation - Alison Lee; Frederick D. King (Cahiers Victoriens et Edouardiens)
‘From Text, to Myth, to Meme: Penny Dreadful and Adaptation’ examines contamination as a form of adaptation in the Showtime/Sky television series Penny Dreadful. According to David Greetham, ‘contamination’ occurs when ‘one mode of discourse . . . leaks into or infects another, so that we experience both at the same time.’ Lee and King argue that contamination is a model of adaptation. The series is self-conscious about its status as adaptation, and uses ideas of parenthood and theatricality in order to bring attention to the adaptation’s relationship to an originary text. Challenging linear and genetic models of adaptation, Penny Dreadful transforms Mary Shelley’s Frankenstein (1818, 1831), Oscar Wilde’s The Picture of Dorian Gray (1890, 1891), and Bram Stoker’s Dracula (1897) into vehicles of cultural transmission: memes that have come to redefine the viewer’s relationship to Victorian literature and culture as a myth of modernity.